The problem of four fours and creative thinking in mathematics: the art of playing with numbers - Gontijo, Cleyton Hércules (Farol, 2024)
The aim of this article is to point out the potential of arithmetic problems to stimulate creative thinking in mathematics. To this end, it focuses on an old problem, known as the problem of four fours, presenting some historical elements related to it and its application in creativity tests in mathematics. In the conclusion, it reflects on activities that can be developed in the school context to stimulate creativity in mathematics.
Keywords: four fours problem; creative thinking in mathematics; creativity in mathematics